2015
DOI: 10.3109/13813455.2015.1031140
|View full text |Cite
|
Sign up to set email alerts
|

Implementing diabetes self-management education (DSME) in a Nigerian population: perceptions of practice nurses and dieticians

Abstract: Hyperglycaemic complication is the most common cause of hospitalization amongst diabetes patients in Nigeria. Research showed that diabetes self-management education (DSME) assists in controlling hyperglycaemia in diabetes patients. We assessed the opinions of practice nurses and dieticians on implementing DSME in a Nigerian population. 517 nurses and dieticians completed a self-administered questionnaire tool. Results showed that the majority of the participants agreed that DSME in a Nigerian population will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…These affirmations are in keeping with nurses in other regions. In Nigeria, Nwankwo et al [10] showed in their research study where majority of the nurses indicated that they believed that DSME would [14] .…”
Section: Section A: Discussion Related To Chns' Perception Of Dsmementioning
confidence: 99%
“…These affirmations are in keeping with nurses in other regions. In Nigeria, Nwankwo et al [10] showed in their research study where majority of the nurses indicated that they believed that DSME would [14] .…”
Section: Section A: Discussion Related To Chns' Perception Of Dsmementioning
confidence: 99%
“…Clearly though, a major barrier (probably the biggest) to implementing effective DSME programmes in Nigeria and other LMICs is the issue of cost and resources. For example, whilst Nigerian nurses and dieticians overwhelmingly support the introduction of DSME programmes, believing them to be of benefit for their patients, only around one-third believe their establishments would be currently capable of implementing them [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Health education is an effective strategy to improve self-care skills including self-management behavior, HbA1c, and blood sugar control, body weight, improve quality of life, decrease stress and increase adherence to medication behavior. 4,5,[17][18][19] Therefore, health education with DSME provides an advantage for patients in order to optimize the 3 components of behavior in self-care of chronic illness. According to the research conducted by Abdulrahman et al 20 provides results that increasing knowledge with health education will increase understanding on the importance of self-care followed by increased behavior.…”
Section: Resultsmentioning
confidence: 99%